2016
DOI: 10.1038/srep24227
|View full text |Cite
|
Sign up to set email alerts
|

A disulphide isomerase gene (PDI-V) from Haynaldia villosa contributes to powdery mildew resistance in common wheat

Abstract: In this study, we report the contribution of a PDI-like gene from wheat wild relative Haynaldia villosa in combating powdery mildew. PDI-V protein contains two conserved thioredoxin (TRX) active domains (a and a′) and an inactive domain (b). PDI-V interacted with E3 ligase CMPG1-V protein, which is a positive regulator of powdery mildew response. PDI-V was mono-ubiquitinated by CMPG1-V without degradation being detected. PDI-V was located on H. villosa chromosome 5V and encoded for a protein located in the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…PDI genes have been previously shown to be contributed against powdery mildew resistance in common wheat [ 36 ]. In this study, we have analyzed expression profiles of these genes in response to Fusarium oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 99%
“…PDI genes have been previously shown to be contributed against powdery mildew resistance in common wheat [ 36 ]. In this study, we have analyzed expression profiles of these genes in response to Fusarium oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 99%
“…Further characterization of the promoter region against powdery mildew suggested that the PromoPDI-V was barely active in response to Bgt. Our previous study showed the upregulation of PDI-V expression upon Bgt infection and its role in combating powdery mildew (Faheem et al, 2016). Therefore, we may speculate on two possibilities for the redundancy of PDI-V promoters against pathogens; firstly, the function of 5′-UTR.…”
Section: Discussionmentioning
confidence: 96%
“…The PCR product and the pAN580 vector were digested by XbaI and SmaI, and the fragments were ligated to produce the fusion gene expression vector p35S::HvSERK2-GFP::Nos3. For transient expression in onion, the constructs were delivered to epidermal cells on the adaxial surfaces of tissue peeled from an onion by particle bombardment, as described by Faheem et al [ 31 ]. GFP signals were assessed by OLYMPUS SZX16 (OLYMPUS, Tokyo, Japan) imaging 16–20 h after bombardment.…”
Section: Methodsmentioning
confidence: 99%
“…The HvSERK2 promoter was cloned into plant expression vector pAN580 [ 31 ] by replacing the CaMV 35S promoter to produce a pAN580:HvSERK2P:GFP plasmid ( Supplementary Materials Table S3 ). Second leaves of one-week-old barley seedlings were firmly placed on the 1% agar plates and were supplemented with 85 µM of benzimidazoles for the delivery of the pAN580:HvSERK2P:GFP plasmid into host cells by gene gun.…”
Section: Methodsmentioning
confidence: 99%